Zebrafish Embryo as an Emerging Model Organism in Neurodevelopmental Toxicity Research - Şükriye Çalışkan; Ebru Emekli Alturfan (European Journal of Biology)
Zebrafish is a model organism that has become increasingly popular in recent years due to some of the advantages it has when compared to traditional model organisms. Its genetic similarity with humans has contributed significantly to the elucidation of the molecular mechanisms underlying diseases. Moreover, external fertilization and rapid embryonic development of zebrafish embryos have made it attractive in many research areas. The genome of humans and zebrafish are found to be highly conserved having 76-82 % of the disease genes in humans that are also present in zebrafish. Zebrafish have been used in different studies in several concepts of neurogenesis. Unlike mammals, the external development of a zebrafish embryo makes it accessible for experimental manipulation in central nervous system research. It was observed that neurotoxic agents induced similar responses to other vertebral models in zebrafish embryos, whose brain development and blood-brain barrier were similar to those of other vertebrates. This review provides brief information about the availability of zebrafish embryos in neurodevelopmental toxicity research while giving brief information on embryogenesis and neurogenesis in zebrafish. Evaluation of neurotoxicity and the specific effects of various neurotoxins on motor and dopaminergic neurons, neuronal proliferation, mobility, and neurodevelopment are also explained.